Climat et biocontamination. Études de cas d’archives - Alain Roche; Sébastien Gilot (In Situ)
Following problems of microbiological contamination of documents in archives, we were repeatedly appointed to evaluate the biocontamination levels and propose recommendations and solutions. It is from the study of both climate and biocontamination that we were able, in most of the cases, to relate the observed fungal situations to their likely causes. We present in this article two cases which seemed to us interesting and complementary: the consequences of dysfunctions of an air handling system and the instability of climates produced by a Mechanical Extract Ventilation system. Even if the fungal situations seem identical, causes of fungal growth can vary greatly. Thus, it is essential to go back up to the origins of the dysfunctions and climate instabilities. The microbiological study states levels of viable species on documents, in environment and in the ambient air. It localizes the areas of strong concentration that it connects directly to the microclimate data collected in the storerooms. Thus while leaning on the study of the microclimates, on the analysis of climate-related events in archives and environmental weather conditions one can hope to determine the factors of contamination.